2012
DOI: 10.1515/cclm-2011-0820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coagulation factors on discrepancies in International Normalized Ratio results between instruments

Abstract: By correcting for the appropriate coagulation factors, especially the systematic differences, but also the between- and within-subject variation of the differences between instruments, were reduced. This indicates that different levels of coagulation factors in the plasma of the patients play an important role in explaining discrepancies between INR instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In a cohort of non-APS patients, Solvik et al demonstrated that different plasma levels of coagulation factors (i.e. fibrinogen, factors II, VII, IX and X) in blood samples from anticoagulated patients play an important role in explaining discrepancies between the different INR test methods [26]. Additionally, the tissue factor content, the phospholipid composition and differences in ISI calibration may contribute to differences observed in the INR measurements using different thromboplastins [5,9,14].…”
Section: Inr Differences Between Different Pt Assaysmentioning
confidence: 99%
“…In a cohort of non-APS patients, Solvik et al demonstrated that different plasma levels of coagulation factors (i.e. fibrinogen, factors II, VII, IX and X) in blood samples from anticoagulated patients play an important role in explaining discrepancies between the different INR test methods [26]. Additionally, the tissue factor content, the phospholipid composition and differences in ISI calibration may contribute to differences observed in the INR measurements using different thromboplastins [5,9,14].…”
Section: Inr Differences Between Different Pt Assaysmentioning
confidence: 99%
“…This is in accord with previous findings, showing that different coagulation factor levels in plasma may play a role in justifying discrepancies between POC-INR instrumentation. 19 The plasma source used by UK NEQAS was not disclosed in their publication, 8 but personal communications from NEQAS identify the source as primarily patient derived. This likely helps (at least in part) explain the relatively lower CVs from UK NEQAS compared with RCPAQAP.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several factors, including antiphospholipid syndrome, heparinization, and use of oral anticoagulants, may cause over or underestimation of the results. [18][19][20][21] In the liver transplant population specifically, endogenous heparinoids released in liver failure, residual exogenous heparin from the donor harvesting procedures, and the effects of recombinant tissue plasminogen activator (administered into the hepatic graft as part of some donation after cardiac death protocols) may be contributory to inaccuracies in the measures. 1,22 The HEMOCHRON Jr. Signature utilizes light-emitting diode optical detectors to determine clot formation below a predetermined threshold.…”
Section: Discussionmentioning
confidence: 99%